Toothbrushing Competency Among High-risk Grade One Students: an Evaluation of Two Methods of Dental Health Education - Robert J. Hawkins, BSc, DDS; Debra L. Zanetti, MEd; Patricia A. Main, DDS, DDPH, MSc, FRCD(C) (Blackwell Synergy, 2001)
To evaluate the effectiveness of two methods of dental health education (DHE) for improving toothbrushing competency among grade one students at high risk for dental diseases.